Inequality and relative saving rates at the top - Philipp Lieberknecht; Philip Vermeulen (European Central Bank (ECB), 2018)
We estimate the long- and short-run relationship between top income and wealth shares for France and the US since 1913. We find strong evidence for a long-run cointegration relationship governed by relative saving rates at the top. For both countries, we estimate a decline in the relative saving rates at the top - after 1968 in France and 1983 in the US, equivalent to a reduction of the long-run gap between wealth and income inequality compared to the period before. In the short-run, income inequality drives wealth inequality, while the converse link is weaker and slower. Using counterfactual simulations, we find that the recent rise in wealth inequality in the US is largely attributable to the contemporary increase in income inequality. Modest income concentration dynamics and a stronger decline in relative saving rates at the top than in the US contributed to a more subdued rise in wealth inequality in France.
Keywords: D31; E21; E25; N32; N34; 330; Income inequality; wealth inequality; VECM; cointegration; top shares